2004
DOI: 10.1111/j.1442-9071.2004.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of intraocular hydrogel lens: evidence of dystrophic calcification

Abstract: This study confirms and extends the previous reports of five cases of calcification of hydrogel intraocular lenses. The exact mechanism of calcification remains obscure but evidence suggesting cell-mediated dystrophic calcification of the lens surface is presented. Further study is required to monitor the incidence and development of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
(19 reference statements)
1
12
2
Order By: Relevance
“…Our findings confirm that the grains deposited on the central part of the intraocular lens contain hydroxyapatite and this could be due to calcification of the remnants of degenerate epithelial cells associated with the lens surface [9]. Because it was demonstrated that lens epithelial cells can act as phagocytes, i.e.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Our findings confirm that the grains deposited on the central part of the intraocular lens contain hydroxyapatite and this could be due to calcification of the remnants of degenerate epithelial cells associated with the lens surface [9]. Because it was demonstrated that lens epithelial cells can act as phagocytes, i.e.…”
Section: Resultssupporting
confidence: 72%
“…The size and shape of the deposited grains suggest, to some extent, a similarity with cells. It was already considered the possibility that these depositions represent dystrophic calcification of the remnants of degenerate epithelial cells associated with the lens surface [9]. With respect to this, we could explain the relatively high nitrogen content determined by XPS in the calcified grains.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the exact cause of opacification and/or calcification for both samples is yet unknown, several factors may be proposed as follows: (1) oxidative stress in the cell-mediated mechanism such as peroxidative reactions within the cellular matrix of the lens tissues; (2) patient's associated conditions including the age, medical history, risk factors and aetiology, clinical features, pathogenesis, prognosis and treatment; (3) production processes of the lens manufacturer during polymer selection, component, manufacturing techniques and processes, and packaging; (4) surgical settings and techniques of clinicians and adjuvants used; (5) environmental and other internal factors [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%